2018
DOI: 10.3390/beverages4040105
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Sustainability of the Coffee Agro-Industry: Spent Coffee Grounds as a Source of New Beverages

Abstract: This work describes a new process for the production of beverages from spent coffee grounds (SCG), as well as the chemical and sensory profiles. The process consisted of the extraction of antioxidant phenolic compounds of SCG, followed by the fermentation of this extract supplemented with sucrose and fermented broth distillation. Thus, two fermented (10.4% and 10.0% of ethanol, by volume) and two distillated (38.1% and 40.2% of ethanol, by volume) beverages were obtained. A total of 45 and 59 volatile compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 31 publications
(48 reference statements)
3
20
1
Order By: Relevance
“…SCG is a nonedible resource, which is not entering into the food chain, and its disposal in the environment is dangerous since SCG contains caffeine, tannins, and polyphenols that make it a toxic residue [6,7]. On these bases, numerous authors have suggested different ways to recycle SCG, to manage and reduce its disposal [8][9][10]. SCG can be used as a source of oil for biodiesel production [11][12][13] or as a source of recoverable sugars which can be employed as food addictive or for bioethanol production [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…SCG is a nonedible resource, which is not entering into the food chain, and its disposal in the environment is dangerous since SCG contains caffeine, tannins, and polyphenols that make it a toxic residue [6,7]. On these bases, numerous authors have suggested different ways to recycle SCG, to manage and reduce its disposal [8][9][10]. SCG can be used as a source of oil for biodiesel production [11][12][13] or as a source of recoverable sugars which can be employed as food addictive or for bioethanol production [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Coffee companies generate a significant amount of liquid and solid wastes (by-products); around 90% of the weight of coffee cherries (mostly pulp) is discarded during processing as agricultural waste or by-product [ 1 ]. Several authors have previously proposed different approaches to reuse the coffee by-products in order to reduce their disposal [ 2 , 3 , 4 , 5 , 6 , 7 ]. Among these by-products is coffee silverskin (CS), which is the major residue generated during the roasting process.…”
Section: Introductionmentioning
confidence: 99%
“…3 For this reason, in the latest years, several authors have proposed original mechanisms to reuse SCG, in order to manage and reduce its disposal. [4][5][6][7][8] Some of them have suggested the used of SCG as a source of oil for biodiesel production; 5 others have proposed the application of SCG as a source of recoverable sugars that can be extracted and employed as food addictive or for bioethanol production. [9][10][11][12] Several works have reported the study of SCG constituents and their application in the food and nutraceutical industries.…”
Section: Introductionmentioning
confidence: 99%
“…Annually, it has been estimated that about 6 million tons of SCG are produced worldwide 3 . For this reason, in the latest years, several authors have proposed original mechanisms to reuse SCG, in order to manage and reduce its disposal 4–8 . Some of them have suggested the used of SCG as a source of oil for biodiesel production; 5 others have proposed the application of SCG as a source of recoverable sugars that can be extracted and employed as food addictive or for bioethanol production 9–12 .…”
Section: Introductionmentioning
confidence: 99%